2022
DOI: 10.3390/su141610083
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Teachers’ Fertility Willingness under China’s ‘Third-Child’ Policy

Abstract: This study aimed to understand whether Chinese early childhood (EC) teachers are willing to give birth to children to embrace the new ‘third-child’ policy. Altogether, 1042 participants (44.7% teachers, 55.3% other parents) were sampled and surveyed online. The results indicated that: (1) the teachers demonstrated fertility willingness different from other parents, and a higher percentage of teachers believed that one child would suffice; (2) the teachers highly valued partner’s support (family), employers’ su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Contribution 3 investigated Chinese early childhood teachers' willingness to have more children under the three-child policy [11]. Compared to other professionals, this study showed that kindergarten teachers had a lower willingness to have an extra child.…”
Section: Fertility Willingness and Childcare Services In Aging Chinamentioning
confidence: 92%
“…Contribution 3 investigated Chinese early childhood teachers' willingness to have more children under the three-child policy [11]. Compared to other professionals, this study showed that kindergarten teachers had a lower willingness to have an extra child.…”
Section: Fertility Willingness and Childcare Services In Aging Chinamentioning
confidence: 92%
“…The factors affecting fertility intentions are very complex and have been the subject of a great deal of scholarly research [ 34 , 52 , 53 ]. Research indicates that at the micro level, fertility intentions are related to factors such as working conditions [ 54 ], economic conditions [ 34 , 52 , 55 ], housing conditions [ 53 ], gender role attitudes [ 56 , 57 ], and family support [ 58 ], while at the macro level, fertility intentions are related to family policy and fertility policy, among other factors. Some scholars argue that economic conditions have a substitutionary effect on fertility intentions, i.e., the better a couple’s economic conditions, the lower their fertility intentions [ 59 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have conducted many studies on the factors influencing the fertility intentions of the general population to have a second child [ 32 , 33 ]. To date, there have been few studies on the fertility intentions of specific groups of people, and only a small number of scholars have studied the fertility intentions of specific samples of people such as early childhood teachers [ 34 ], college students [ 35 ], and transient population [ 36 ]. The study of special groups in this paper is motivated by concerns about policy implications, improvements in policy design.…”
Section: Introductionmentioning
confidence: 99%